Carbon Monoxide in Pancreatic Islet Transplantation: A New Therapeutic Alternative to Patients With Severe Type 1 Diabetes Mellitus - Dugbartey, George J. (Frontiers in Pharmacology, 2021)
Pancreatic islet transplantation is a minimally invasive procedure to replace β-cells in a subset of patients with autoimmune type 1 diabetic mellitus, who are extremely sensitive to insulin and lack counter-regulatory measures, and thereby increasing their risk of neuroglycopenia and hypoglycemia unawareness. Thus, pancreatic islet transplantation restores normoglycemia and insulin independence, and prevents long-term surgical complications associated with whole-organ pancreas transplantation. Nonetheless, relative inefficiency of islet isolation and storage process as well as progressive loss of islet function after transplantation due to unvoidable islet inflammation and apoptosis, hinder a successful islet transplantation. Carbon monoxide (CO), a gas which was once feared for its toxicity and death at high concentrations, has recently emerged as a medical gas that seems to overcome the challenges in islet transplantation. This minireview discusses recent findings about CO in preclinical pancreatic islet transplantation and the underlying molecular mechanisms that ensure islet protection during isolation, islet culture, transplantation and post-transplant periods in type 1 diabetic transplant recipients. In addition, the review also discusses clinical translation of these promising experimental findings that serve to lay the foundation for CO in islet transplantation to replace the role of insulin therapy, and thus acting as a cure for type 1 diabetes mellitus and preventing long-term diabetic complications.